Proses Pembuatan Mesin Pengiris Buah Pinang Model Pisau Rotari Kapasitas 25 Kg/Jam - Irfansyah, M.; Lubis, Zulkifli; Oppusunggu, Kamrul; Nurdiana, Nurdiana (CV. IRA PUBLISHING, 2022)
Areca fruit slicing machine, with a capacity of 25 kg/hour, has a machine construction consisting of a drive mechanism, an inlet mechanism, an outlet mechanism and a slicing mechanism. The areca fruit slicing mechanism uses the main components such as the pressure handle, inlet, disc carrying the blade, and the slicing knife. At the same time, the drive mechanism uses supporting components such as intermediate shafts, reducers, gears, pulleys and belts. The manufacture of this machine uses machine tools, including lathes, grinding machines, cutting grinding machines, drill/drilling machines, milling machines and welding machines. At the same time, the components made include the machine frame, drive shaft, pressure handle, slicing blade, disc carrying blade, inlet, outlet, and casing cover. Time calculation can be done by planning the work steps of the manufacturing process for each component, including the procurement of materials, measurements, processes, time intervals (wasted time) and finishing. From the work results, it was obtained that the total time for making eight components and assembling was 1094.48 minutes (18.24 hours).